A Combined Softening and Hardening Mechanism for Low Frequency Human Motion Energy Harvesting Application - Azma, Putra; Khalis, Suhaimi; Roszaidi, Ramlan (Hindawi, 2014)
This paper concerns the mechanism for harvesting energy from human body motion. The vibration signal from human body motion during walking and jogging was first measured using 3-axes vibration recorder placed at various places on the human body. The measured signal was then processed using Fourier series to investigate its frequency content. A mechanism was proposed to harvest the energy from the low frequency-low amplitude human motion. This mechanism consists of the combined nonlinear hardening and softening mechanism which was aimed at widening the bandwidth as well as amplifying the low human motion frequency. This was realized by using a translation-to-rotary mechanism which converts the translation motion of the human motion into the rotational motion. The nonlinearity in the system was realized by introducing a winding spring stiffness and the magnetic stiffness. Quasi-static and dynamic measurement were conducted to investigate the performance of the mechanism. The results show that, with the right degree of nonlinearity, the two modes can be combined together to produce a wide at response. For the frequency amplification, the mechanism manages to increase the frequency by around 8 times in terms of rotational speed.